Macro-financial models of Canadian dollar interest rate swap yields - Tanweer Akram; Khawaja Mamun (Levy Economics Institute of Bard College, 2024)
This paper analyzes the dynamics of Canadian dollar-denominated (CAD) interest rate swap yields. It applies autoregressive distributive lag (ARDL) models, using monthly time series data, to estimate the effects of the current short-term interest rate and other relevant macro-financial variables on interest rate swap yields. It shows that the current short-term interest rate is a crucial driver of the swap yields of different maturity tenors. Similar patterns of interest rate swaps denominated in other hard currencies, such as the US dollar, euro, British pound sterling, and Japanese yen, have been discerned in previous empirical research testing the Keynesian hypothesis, which maintains that the current short-term interest rate has a decisive influence on the long-term interest rate. Thus, the findings of this paper lend additional support to the Keynesian hypothesis by showing that the same pattern holds for CAD interest rate swap yields. The results obtained in the paper can be useful for portfolio managers, corporate leaders, and policymakers.
Keywords: E43; E50; E60; G10; G12; 330; Canadian Dollar Swaps; Interest Rate Swap Yields; Short-Term Interest Rate; Monetary Policy; Bank of Canada